Effect of Sheet Resistance and Morphology of ITO Thin Films on Polymer Solar Cell Characteristics - Ram Narayan Chauhan; C. Singh; R. S. Anand; Jitendra Kumar (International Journal of Photoenergy, 2012)
Solar cell fabrication on flexible thin plastic sheets needs deposition of transparent conducting anode layers at low temperatures. ITO thin films are deposited on glass by RF sputtering at substrate temperature of 70∘C and compare their phase, morphology, optical, and electrical properties with commercial ITO. The films contain smaller nanocrystallites in (222) preferred orientation and exhibit comparable optical transmittance (~95%) in the wavelength range of 550–650 nm, but high sheet resistance of ~103 Ω/□ (the value being ~36 Ω/□ for commercial ITO).The polymer solar cells with PEDOT: PSS and P3HT: PCBM layers realized on RF sputtered vis-a-vis commercial ITO thin films are shown to display a marginal difference in power conversion efficiency, low fill factor, and low open-circuit voltage but increased short-circuit current density. The decrease in fill factor, open-circuit voltage is compensated by increased short-circuit current. Detailed study is made of increased short-circuit current density.